Measuring resilience properties of household livelihoods and food security outcomes in the risky environments of Ethiopia - Kasie, Tesfahun Asmamaw; Tsegaye, Enyew Adgo; Grandío-Botella, Antonio; Giménez-García, Isabel (Iberoamerican Journal of Development Studies, 2018)
The purpose of this study is to contribute to efforts to measuring and assessing resilience properties of household livelihoods constructed in the risky environments. It provides new insights for assessing vulnerability of household livelihoods and designing resilience building programs in areas of protracted food crisis. Based on resilience theory as applied to social-ecological systems with an application of Modern Portfolio Theory, we adapted and measure the four properties of resilience to livelihood systems and tested the expected relationships between system properties as predicted by resilience theory. Household livelihood systems exhibited the expected pattern of increasing connectivity with increasing wealth (food income). Similarly, household resilience to food insecurity increases with increasing diversity of livelihood options and diversity declines with increasing connectivity of the system. This study confirms the key role of livelihood diversification for improving household resilience to food insecurity at both higher and lower wealth groups of households.